Peran Usaha Kerajinan Tamas dalam Meningkatkan Kesejahteraan Keluarga di Desa Depeha Kecamatan Kubutambahan Kabupaten Buleleng - Widhiarti, Ni Putu; Sujana, I Nyoman (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research aims to understand the role of tamas handicraft businesses in improving family welfare. The study employs a descriptive qualitative approach. The subjects of this research are 20 tamas artisans in the village of Depeha. Data were collected through observation, interviews, and documentation. Data were obtained through semi-structured interviews with 20 informants. The data analysis techniques used include data reduction, data presentation, and conclusion drawing or verification. The findings indicate that the tamas handicraft business, carried out by housewives, can help improve their families' welfare, even though the income from the tamas handicraft business is still below the primary income of the artisans' families. These results are significant for tamas artisans, particularly in increasing knowledge in the field of more effective processing and marketing, so that the obtained results can be maximized, which will certainly impact the welfare of the artisans' families.